Survival, Recurrence, and Function After Epiphyseal Preservation and Allograft Reconstruction in Osteosarcoma of the Knee - Aponte-Tinao, Luis (Clin Orthop Relat Res, 2014)
BACKGROUND: Bone tumor resections for limb salvage have become the standard treatment. Recently, intercalary tumor resection with epiphyseal sparing has been used as an alternative in patients with osteosarcoma. The procedure maintains normal joint function and obviates some complications associated with osteoarticular allografts or endoprostheses; however, long-term studies analyzing oncologic outcomes are scarce, and to our knowledge, the concern that a higher local recurrence rate may be an issue has not been addressed. QUESTIONS/PURPOSES: We wanted to assess (1) the overall survival in patients treated with this surgical technique; (2) the percentage of local recurrence and limb survival, specifically the incidence of recurrence in the remaining epiphysis; (3) the frequency of orthopaedic complications, and, (4) the functional outcomes in patients who have undergone intercalary tumor resection. METHODS: We analyzed all 35 patients with osteosarcomas about the knee (distal femur and proximal tibia) treated at our center between 1991 and 2008 who had resection preserving the epiphysis and reconstruction with intercalary allografts. Minimum followup was 5 years, unless death occurred earlier (mean, 9 years; range, 1–16 years), and no patients were lost to followup. During the study period, our indications for this approach included patients without metastases, with clinical and imaging response to neoadjuvant chemotherapy, that a residual epiphysis of at least 1 cm thickness could be available after a surgical margin width in bone of 10 mm was planned, and 16% of patients (35 of 223) meeting these indications were treated using this approach. Using a chart review, we ascertained overall survival of patients, oncologic complications such as local recurrence and tumor progression, limb survival, and orthopaedic complications including infection, fracture, and nonunion. Survival rates were estimated using the Kaplan-Meier method. Patient function was evaluated using the Musculoskeletal Tumor Society (MSTS)-93 scoring system. RESULTS: Overall survival rate of the patients was 86% (95% CI, 73%–99%) at 5 and 10 years. Five patients died of disease. No patient had a local recurrence in the remaining bony epiphysis, but three patients (9%; 95% CI, 0%–19%) had local recurrence in the soft tissue. The limb survival rate was 97% (95% CI, 89%–100%) at 5 and 10 years. Complications treated with additional surgical procedures were recorded for 19 patients (54%), including three local recurrences, two infections, 11 fractures, and three nonunions. In 10 of these 19 patients, the allograft was removed. Only five of the total 35 study patients (14%) lost the originally preserved epiphysis owing to complications. The mean functional score was 26 points (range, 10–30 points, with a higher score representing a better result) at final followup. CONCLUSIONS: Although the recurrence rate was high in this series, the small sample size means that even one or two fewer recurrences might have resulted in a much more favorable percentage. Because of this, future, larger studies will need to determine whether this is a safe approach, and perhaps should compare epiphyseal preservation with other possible approaches, including endoprosthetic reconstruction and/or osteoarticular allografts. LEVEL OF EVIDENCE: Level IV, therapeutic study.